A Study of the Critical Views of Kurdish Intellectual Poets on Mysticism and Sufism - Jamal Ahmadi (پژوهشنامه ادبیات کردی, 2022)
Throughout history, mysticism and Sufism have been criticized by scholars and even mystics themselves. Some scholars, who can be called “Salafis,” have not accepted mysticism and Sufism and have constantly rejected them from the past to this day. Still, some scholars criticized them logically, mentioning their advantages and disadvantages. The Kurdish community is a Muslim community, and, like other Islamic communities, Sufism is practiced in it. Without being ungrateful to some of the Sheikhs and Sufis and their efforts, in many Kurdish literary texts, especially poetry, they have been regarded as obstacles to the Kurdish people’s progress and have been sharply criticized. The present study aims to examine the views of Kurdish intellectual poets scientifically regarding mysticism, and Sufism in Kurdistan, especially during the time of Haji Qadir and shortly after that. It seeks to find the reasons behind the hostility and harsh criticisms of Kurdish intellectual poets towards the mystics and Sufis of Kurdistan - especially Sufism, which has deviated from its path - adopting the content analysis method and using library resources. The results of the research indicates that based on the views of intellectual poets, laziness, unemployment, carnal inclinations, considering themselves an exalted position, exploitation of people, self-conceit, and hypocrisy of many Sufis, were factors contributing to the ignorance of people and created some obstacles in the way of the development of Kurdish society.